Improving the Health of Maine, One Employee at a Time - Whalen, Jerry (Maine Policy Review, 2008)
In this commentary, Jerry Whalen, an officer in Eastern Maine Healthcare Systems, discusses employee wellness programs and the importance of focusing on the workplace. He notes that managers and senior executives have a key role to play in ensuring success of employee wellness programs